Inventarization Macroscopic Fungi at Tegallega Resort Taman Gunung Gede Pangrango National Park - Nabila Khusnul Cahyaningtyas; Husnin Nahry Yarza (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
This study aims to inventory macroscopic fungi at Resort Tegallega, Gunung Gede Pangrango National Park conducted at three tracking locations. The research method used is descriptive qualitative and with the cruise data collection method (cruise method) by tracing the research location points. The results obtained based on the research that has been done, it was found that most of the fungi belong to the phylum Basidiomycota and only one type of fungus belongs to the phylum Ascomycota. The environmental conditions where mushrooms grow are not that much different, because the three tracking points are still in the same area.